A New Optimal DTC Switching Strategy for Open-End Windings Induction Machine using Dual Inverter - Nabilah Aisyah; Maaspaliza Azri; Auzani Jidin; M. Z. Aihsan; MHN Talib (Institute of Advanced Engineering and Science, 2021)
Since the early 1980s, fast torque dynamic control has been a subject of research in AC drives. To achieve superior torque dynamic control, two major techniques are used, namely Field Oriented Control (FOC) and Direct Torque Control (DTC), spurred on by rapid advances in embedded computing systems. Both approaches employ the space vector modulation (SVM) technique to perform the voltage source inverter into over modulation region for producing the fastest torque dynamic response. However, the motor current tends to increase beyond its limit (which can damage the power switches) during the torque dynamic condition, due to inappropriate flux level (i.e. at rated stator flux). Moreover, the torque dynamic response will be slower, particularly at high speed operations since the increase of stator flux will produce negative torque slopes more often. The proposed research aims to formulate an optimal switching modulator and produce the fastest torque dynamic response. In formulating the optimal switching modulator, the effects of selecting different voltage vectors on torque dynamic responses will be investigated. With greater number of voltage vectors offered in dual inverters, the identification of the most optimal voltage vectors for producing the fastest torque dynamic responses will be carried out based on the investigation. The main benefit of the proposed strategy is that it provides superior fast torque dynamic response which is the main requirements for many AC drive applications, e.g. traction drives, electric transportations and vehicles.